1990
DOI: 10.1111/j.1751-1097.1990.tb01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cyclobutane Thymine Dimers Photosensitized by Pyridopsoralens: A Triplet‐triplet Energy Transfer Mechanism

Abstract: The 365 nm irradiation of thymine thin films in the presence of pyridopsoralens is shown to induce the formation of cyclobutane thymine dimers, in contrast to other compounds such as 8- and 5-methoxypsoralen. In order to elucidate the mechanism of such a photosensitized reaction, we have determined the energy of the lowest triplet state (T1) of these compounds, using phosphorescence spectroscopy and CNDO/S quantum chemistry calculations. The T1 energy values were found to be significantly higher for pyridopsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
(17 reference statements)
4
16
0
Order By: Relevance
“…There is an abundant literature on the TTET-mediated formation of CPDs in ds DNA by several photosensitizers, including acetone (142), acetophenone (54,142), benzophenone (54,143), carprofen (144), fenofibric acid (143), fluoroquinolones (92,93,145), ketoprofen (143) and three pyridopsoralen derivatives (146,147). The predominant CPD photoproduct of the latter photosensitized reactions was found to be cis-syn T<>T, in agreement with the fact that thymine exhibits the lowest triplet energy (E T ) among nucleobases (148).…”
Section: Triplet Energy Transfersupporting
confidence: 72%
“…There is an abundant literature on the TTET-mediated formation of CPDs in ds DNA by several photosensitizers, including acetone (142), acetophenone (54,142), benzophenone (54,143), carprofen (144), fenofibric acid (143), fluoroquinolones (92,93,145), ketoprofen (143) and three pyridopsoralen derivatives (146,147). The predominant CPD photoproduct of the latter photosensitized reactions was found to be cis-syn T<>T, in agreement with the fact that thymine exhibits the lowest triplet energy (E T ) among nucleobases (148).…”
Section: Triplet Energy Transfersupporting
confidence: 72%
“…In DNA, where the thymine triplet energy has been estimated to be about 270 kJ mol À1 , [8] several types of molecules can be at the origin of CPD formation: ketonic derivatives such as acetone, acetophenone or benzophenone, [9][10][11] non-steroidal anti-inflammatory drugs or their photoproducts such as ketoprofen, tiaprofenic acid, and indoprofen, [12][13][14] psoralens, and fluoroquinolones. [15,16] Laser flash-photolysis experiments have shown that the triplet-triplet absorption of isolated thymidine can be observed upon quenching of the triplet states with energy as low as 310 kJ mol…”
Section: Introductionmentioning
confidence: 99%
“…Pyridopsoralen can form only 4'3'-monoadduct with DNA due to the pyridine ring fused at the 3,4-double bond and consequently shows lower phototoxic effects. Pyridopsoralen shows relatively low triplet quantum yield (aT -0.02 (16)) and the photoreaction of PyPs is very likely to proceed via the singlet excited state even though the for- mation of triplet PyPs in the DNA-intercalated complex was reported recently (17). The 365 nm irradiation of PyPs-thymidine and of PyPs-DNA aqueous solution was found to lead to the formation of cyclobutane thymidine dimer, in addition to 4',5'-monoadduct as a major product.…”
Section: Introductionmentioning
confidence: 99%